Fiscal multipliers and time preference - Gilberto Marcheggiano; David Miles (Bank of England, External Monetary Policy Committee Unit, 2013)
This paper explores the links between fiscal multipliers and household discount rates. We report evidence of a large and statistically significant relationship between reported rates of time preference across countries and the government expenditure multiplier. This study uses recent cross-country data on reported rates of time preferences gathered by Wang, Rieger and Hens (2011). We find that a higher reported rate of time preference is strongly associated with a larger government expenditure multiplier. Our findings may help to explain some of the differences in view over the optimal path for fiscal consolidation in Europe today, between the Germanic and Northern European countries (whose representatives appear to favour a faster fiscal retrenchment) and those in the South (who would like their required fiscal adjustment to occur less rapidly).
Keywords: 330